Gene expression changes in therapeutic ultrasound-treated venous leg ulcers - Boerman, Olivia; Abedin, Zahidur; DiMaria-Ghalili, Rose Ann; Weingarten, Michael S.; Neidrauer, Michael; Lewin, Peter A.; Spiller, Kara L. (Frontiers in Medicine, 2023)
Low-frequency, low-intensity ultrasound has been previously shown to promote healing of chronic wounds in humans, but mechanisms behind these effects are poorly understood. The purpose of this study was to evaluate gene expression differences in debrided human venous ulcer tissue from patients treated with low-frequency (20 kHz), low-intensity (100 mW/cm2) ultrasound compared to a sham treatment in an effort to better understand the potential biological mechanisms. Debrided venous ulcer tissue was collected from 32 subjects one week after sham treatment or low-frequency, low-intensity ultrasound treatment. Of these samples, 7 samples (3 ultrasound treated and 4 sham treated) yielded sufficient quality total RNA for analysis by ultra-high multiplexed PCR (Ampliseq) and expression of more than 24,000 genes was analyzed. 477 genes were found to be significantly different between the ultrasound and sham groups using cut-off values of p<0.05 and fold change of 2. The top differentially regulated genes included those involved in regulation of cell metabolism, proliferation, and immune cell signaling. Gene set enrichment analysis identified 20 significantly enriched gene sets from upregulated genes and 4 significantly enriched gene sets from downregulated genes. Most of the enriched gene sets from upregulated genes were related to cell-cell signaling pathways. The most significantly enriched gene set from downregulated genes was the inflammatory response gene set. These findings show that therapeutic ultrasound influences cellular behavior in chronic wounds as early as one week after application. Considering the well-known role of chronic inflammation in impairing wound healing in chronic wounds, these results suggest that a downregulation of inflammatory genes is a possible biological mechanism of ultrasound-mediated venous chronic wound healing. Such increased understanding may ultimately lead to the enhancement of ultrasound devices to accelerate chronic wound healing and increase patient quality of life.